2017
DOI: 10.1515/ace-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Durability Properties of Engineered Cementitious Composites with Polypropylene Fiber and Glass Fiber

Abstract: The durability characteristics of Engineered Cementitious Composites (ECC) with various fibers such as polypropylene and glass were investigated in view of developing composites with high resistance to cracking. ECC offer large potential for durable civil infrastructure due to their high tensile strain capacity and controlled micro-crack width. In this study, fibre volume fractions (0.5%, 1%, 1.5%, and 2%) of both polypropylene and glass fibers varied and durability measures such as a rapid chloride penetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Following sulfate erosion, concrete expands, cracks, dissolves, peels off, and decreases in strength, which affects the durability of structures. Fiber is a new type of an environmentally friendly and green high-performance material, and can be used in cement materials to improve bending, impact properties, toughness, and corrosion resistance [1][2][3]. In addition, due to the bridging effect of fibers, resistance to crack propagation increases [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Following sulfate erosion, concrete expands, cracks, dissolves, peels off, and decreases in strength, which affects the durability of structures. Fiber is a new type of an environmentally friendly and green high-performance material, and can be used in cement materials to improve bending, impact properties, toughness, and corrosion resistance [1][2][3]. In addition, due to the bridging effect of fibers, resistance to crack propagation increases [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…e concrete with 0.8% PPF content has the smallest expansion rate, which was only 76% of ordinary concrete. Ranjith et al [32] adopt to study the influence of immersing age on the sulfate attack resistant of concrete.…”
Section: Permeabilitymentioning
confidence: 99%
“…ey found that the durability of concrete can be enhanced by adding hybrid fibres. Ranjith et al [32] investigated the durability of engineered cementitious composites reinforced by PPFs and glass fibres. e durability indexes, such as water absorption, chloride penetration, sulfate attack resistance, and acid attack resistance, were enhanced by using PPFs and glass fibres together.…”
Section: Introductionmentioning
confidence: 99%
“…When concrete is used in these projects, the damage and damage of concrete are mainly affected by freeze–thaw and chloride solution 2 . There are several ways to improve the wear and corrosion resistance of face concrete, namely adding polymers, silica fume, plasticizers or reinforcing fibers to the concrete mix, and so forth 3–8 …”
Section: Introductionmentioning
confidence: 99%
“…The addition of fibers is an effective solution to this problem 9 . It was documented by Ranjith et al 8 that, increasing polypropylene and glass fiber content up to 1.5% improved the durability properties of ECC. Adding polypropylene fiber (PPF) into concrete can effectively improve the freezing thawing resistance 10 .…”
Section: Introductionmentioning
confidence: 99%